PENGEMBANGAN MODUL PEMBELAJARAN SIKLUS AKUNTANSI PERUSAHAAN JASA - -, Supardi -; -, Khairinal -; -, Suratno - (Program Magister Teknologi Pendidikan Universitas Jambi, 2011)
This article is based on research and development aimed at producing learning modules for senior high-school students. The module is developed using Dick and Carey’s (2005) model. Based on the data analysis of the development process, experts judgments, evaluation of the product it can be concluded the module is necessary and practicable to use and facilitate students in learning activities, especially in understanding essential concept of Accounting CyclesKeywords: learning module, accounting cycle.